Glacier Mass Changes of Lake-Terminating Grey and Tyndall Glaciers at the Southern Patagonia Icefield Derived From Geodetic Observations and Energy and Mass Balance Modeling - Weidemann, Stephanie S.; Sauter, Tobias; Malz, Philipp; Jaña, Ricardo; Arigony-Neto, Jorge; Casassa, Gino; Schneider, Christoph (Frontiers in Earth Science, 2018)
In this study we demonstrate how energy and mass fluxes vary in space and time for Grey and Tyndall glaciers at the Southern Patagonia Icefield (SPI). Despite the overall glacier retreat of most Patagonian glaciers, a recent increase in mass loss has been observed, but individual glaciers respond differently in terms of spatial and temporal changes. In this context, the detailed investigation of the effect of mass balance processes on recent glacier response to climate forcing still needs refinement. We therefore quantify surface energy-fluxes and climatic mass balance of the two neighboring glaciers, Grey and Tyndall. The COupled Snow and Ice energy and MAss balance model COSIMA is applied to assess recent surface energy and climatic mass balance variability with a high temporal and spatial resolution for a 16-year period between April 2000 to March 2016. The model is driven by downscaled 6-hourly atmospheric data derived from ERA-Interim reanalysis and MODIS/Terra Snow Cover and validated against ablation measurements made in single years. High resolution precipitation fields are determined by using an analytical orographic precipitation model. Frontal ablation is estimated as residual of climatic mass balance and geodetic mass balance derived from TanDEM-X/SRTM between 2000 and 2014. We simulate a positive glacier-wide mean annual climatic mass balance of +1.02$±$0.52\,m\,w.e. a$^{-1}$ for Grey Glacier and of +0.68$±$0.54\,m\,w.e. a$^{-1}$ for Tyndall Glacier between 2000 and 2014. Climatic mass balance results show a high year to year variability. Comparing climatic mass balance results with previous studies underlines the high uncertainty in climatic mass balance modeling with respect to accumulation on the SPI. Due to the lack of observations accumulation estimates differ from previous studies based on the methodological approaches. Mean annual ice loss by frontal ablation is estimated to be 2.07$±$0.70\,m\,w.e.\,a$^{-1}$ for Grey Glacier and 3.26$±$0.82\,m\,w.e.\,a$^{-1}$ for Tyndall Glacier between 2000 and 2014. Ice loss by surface ablation exceeds ice loss by frontal ablation for both glaciers. The overall mass balance of Grey and Tyndall glaciers are clearly negative with -1.05$±$0.18\,m\,w.e.\,a$^{-1}$ and -2.58$±$0.28\,m\,w.e.\,a$^{-1}$ respectively.